2016
DOI: 10.1002/smi.2710
|View full text |Cite
|
Sign up to set email alerts
|

Reaping the benefits of meaningful work: The mediating versus moderating role of work engagement

Abstract: This study examined whether meaningful work may improve one's quality of life outside of the workplace (i.e., work-to-life enrichment). More importantly, we proposed and tested competing hypotheses regarding the role of work engagement in the relationship between meaningful work and work-to-life enrichment. Specifically, we investigated whether work engagement served as a mediator of this relationship, as suggested by the job demands-resources model, or instead a moderator, as suggested by conservation of reso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
43
0
6

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 59 publications
(52 citation statements)
references
References 63 publications
3
43
0
6
Order By: Relevance
“…Firstly, managers need to try and promote work engagement and meaningful work in their Millennial workers to increase the latter's desire to stay longer in their current organization or company. Furthermore, companies also need to adequately facilitate the dimensions of job resources for their workers (Johnson & Jiang, 2017). For example, the management team of the company needs to provide authority for the Millennial workers to increase their self-efficacy, which leads to an increase in their work meaningfulness and engagement (Johnson & Jiang, 2017).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Firstly, managers need to try and promote work engagement and meaningful work in their Millennial workers to increase the latter's desire to stay longer in their current organization or company. Furthermore, companies also need to adequately facilitate the dimensions of job resources for their workers (Johnson & Jiang, 2017). For example, the management team of the company needs to provide authority for the Millennial workers to increase their self-efficacy, which leads to an increase in their work meaningfulness and engagement (Johnson & Jiang, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…The Job Demands-Resources model (JD-R model) can help to understand the relationship between the three concepts, which are meaningful work, work engagement, and turnover intention. The JD-R model explained that job resources could contribute to working engagement, which then potentially created a positive impact on work job resources are described as the aspects of work that can help in reaching work achievement related to the target, increasing the rate of selfgrowth, learning, development, and motivation (Johnson & Jiang, 2017). Therefore, meaningful work can be considered part of job resources because it helps stimulate understanding and purpose in work (Steger & Dik, 2010).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The main objective of this study is to determine the effect of meaningful work on employee identity via the mediating role of employee resilience. Researchers have suggested that work meaningfulness plays a vital role in improving the employees' affective commitment (Johnson & Jiang, 2017) and enhance their ability of innovativeness (Cai et al, 2018). Coutu (2002) also directed researchers to observe the correlation of meaningful work with resilience in future studies.…”
Section: Introductionmentioning
confidence: 99%